A new dye uptake assay to test the activity of antibiotics against intracellular Francisella tularensis - Sutera, Vivien; Caspar, Yvan; Boisset, Sandrine; Maurin, Max (Frontiers in Cellular and Infection Microbiology, 2014)
Francisella tularensis, a facultative intracellular bacterium, is the aetiological agent of tularaemia. Antibiotic treatment of this zoonosis is based on the administration of a fluoroquinolone or a tetracycline for cases with mild to moderate severity, whereas an aminoglycoside (streptomycin or gentamicin) is advocated for severe cases. However, treatment failures and relapses remain frequent, especially in patients suffering from chronic lymph node suppuration. Therefore, new treatment alternatives are needed. We have developed a dye uptake assay for determination of minimal inhibitory extracellular concentrations (MIECs) of antibiotics against intracellular F. tularensis, and validated the method by comparing the results obtained using a CFU-enumerating method. We also compared MIECs with MICs of the same compounds determined using a CLSI broth microdilution method. We tested the activity of 11 antibiotics against two clinical strains of F. tularensis subsp. holarctica isolated in France. Both strains displayed low MICs (≤1 μg/mL) to fluoroquinolones (ciprofloxacin, levofloxacin and moxifloxacin), gentamicin, doxycycline and rifampicin. Higher MICs (≥8 μg/mL) were found for carbapenems (imipenem and meropenem), daptomycin and linezolid. Erythromycin MICs were 4.0 and 16.0 μg/mL, respectively, for the two clinical strains. MIECs were almost the same with the two methods used. They were concordant with MICs, except for erythromycin and linezolid (respectively, four and eight times more active against intracellular F. tularensis) and gentamicin (four to eight times less active against intracellular F. tularensis). This study validated the dye uptake assay as a new tool for determination of the activity of a large panel of antibiotics against intracellular F. tularensis. This test confirmed the intracellular activity of first-line antibiotics used for tularaemia treatment, but also revealed significant activity of linezolid against intracellular F. tularensis.